Membangun Karakter Siswa Sekolah Dasar Melalui Nilai – Nilai Pancasila Dalam Pendidikan : Studi Literatur - Yolanda Veliani Pratama; Ari Suriani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Instilling Pancasila values from an early age serves as a crucial foundation in shaping the character of elementary school students, particularly amidst the challenges posed by digitalization and globalization. This study employs a literature review approach to explore strategies for implementing character education based on Pancasila principles. The analysis encompasses relevant academic sources published between 2020 and 2025. Findings indicate that core values such as tolerance, cooperation, and social justice can be effectively integrated through project-based learning, interactive digital media, and active collaboration between schools and families. Nonetheless, challenges persist, including the influence of unfiltered digital content and discrepancies between home and school environments. This study underscores the need for a holistic approach that incorporates cognitive, affective, and psychomotor dimensions, along with the development of innovative and context-sensitive strategies. The results are expected to contribute to strengthening character education rooted in Pancasila within primary education settings.